2014
DOI: 10.1007/s00220-014-2167-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of Hall Conductance for Interacting Electrons on a Torus

Abstract: We consider interacting, charged spins on a torus described by a gapped Hamiltonian with a unique groundstate and conserved local charge. Using quasi-adiabatic evolution of the groundstate around a flux-torus, we prove, without any averaging assumption, that the Hall conductance of the groundstate is quantized in integer multiples of e 2 /h, up to exponentially small corrections in the linear size L. In addition, we discuss extensions to the fractional quantization case under an additional topological order as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 25 publications
4
119
0
1
Order By: Relevance
“…, P n , we can enclose the points x(f ) belonging to the set P j in a box: in this way, assuming that all the points x(f ), f ∈ ∪ i P i , are distinct, we obtain n disjoint boxes. Given these definitions, if 38) where:…”
Section: B Uniform Analyticity Of the Regularized Correlation Functionsmentioning
confidence: 99%
“…, P n , we can enclose the points x(f ) belonging to the set P j in a box: in this way, assuming that all the points x(f ), f ∈ ∪ i P i , are distinct, we obtain n disjoint boxes. Given these definitions, if 38) where:…”
Section: B Uniform Analyticity Of the Regularized Correlation Functionsmentioning
confidence: 99%
“…In Fig. 2(d), we have numerically observed that the Berry curvature is almost independent of θ's, which implies that the computation of the Chern number may be simplified by defining the non-Hermitian counterpart of the one-plaquet Chern number for the Hermitian case [76][77][78][79]. We leave the extension of oneplaquet Chern number to non-Hermitian systems as a future work.…”
mentioning
confidence: 95%
“…Newer methods for higher-dimensional spin systems are also in development [25]. There has also been several results concerning stability of topological invariants such as the Hall conductance in interacting fermion systems [7,8,9,33,37,47].…”
Section: Introductionmentioning
confidence: 99%